Analysis of Fatwas No. IX: 78/DSN-MUI/IX/2010 on Interbank Money Market in the Maslahah Mursalah Perspective - Ardin Hisyam Maulana Fajar Arjuna; M. Lathoif Ghozali (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
Fatwas issued by DSN-MUI are generally related to sharia banking products and contracts. However, these fatwas cannot be immediately applied in sharia banking operations because they are not part of the legal and regulatory hierarchy. Fatwas NO: 78/DSN-MUI/IX/2010 specifically regulates sharia principles in the mechanisms and instruments of the interbank money market. The formulation of the problem in this research is how is the DSN-MUI fatwas NO: 78/DSN-MUI/IX/2010 reviewed from the perspective of maslahah mursalah? This research uses a library method, with a descriptive approach that prioritizes in-depth analysis of various available sources and data. The results of this study indicate that in the DSN-MUI fatwas NO: 78/DSN-MUI/IX/2010, there are 13 provisions that regulate the interbank money market mechanism based on sharia principles. This is in line with the qualification of maslahah ad-Dharuriyah, namely the benefits related to the basic needs of humans both in the world and the hereafter, and humans cannot survive without wealth/property which is the main element in human life. There are 5 benefits, namely: Hifz ad-Din (preserving the religion), Hifz an-Nafs (preserving the soul), Hifz al-'Aql (preserving the intellect), Hifz an-Nasl (preserving of offspring), Hifz al-Mal (preserving the property), these basic needs are considered non-negotiable and must be prioritized to ensure a just, balanced, and prosperous society.